Vibrational behavior of defective and repaired carbon nanotubes under thermal loading: A stochastic molecular mechanics study. (December 2021) - Payandehpeyman, J.; Moradi, K.; Zeraati, A. Shayesteh; Hosseinabadi, H. Goodarzi
Abstract: Carbon nanotubes (CNTs) are promising candidates for high-resolution mass nanosensors owing to their unique vibrational behavior. The structural characteristic (e.g. defect type and density) and working temperature have a significant effect on the natural frequency of CNT-based sensors. Herein, a stochastic approach based on novel finite element and molecular mechanics simulations is implemented to model the effect of temperature and structural characteristics of single-wall CNTs including defects (vacancy defect with different densities) and chirality (zigzag and armchair) on their vibrational behavior. The results show that the vacancy defects exert a significant deterioration of the average natural frequency to 79.5% and 81.5% of a perfect structure for armchair and zigzag configuration, respectively. This is combined with a significant scattering of natural frequencies that limits the wide application of CNTs for high-resolution mass nanosensors. We originally showed that bond reconstruction/repairing plays an important role in engineering the resonance. The results demonstrate that a binding recovery of a double vacancy improves the average CNTs natural frequency response close to a perfect CNT (93.8% and 94.6% of a perfect CNT for armchair and zigzag configuration, respectively). Moreover, the reconstruction reduces by one-third the standard deviation of CNT natural frequency that increases the accuracy of nano-sensors for detecting very small masses down to zeptogram. These findings can pave the way to design ultra-high resolution CNT-based nano-sensors with different sensitivity using defective and repaired/reconstructed CNTs. Graphical abstract: Highlights: A combined finite element-molecular mechanic is developed to study the effect of defects and defect recovery on the vibrational behavior of single-wall carbon nanotubes (SWCNTs) with armchair and zigzag configurations. The results demonstrate that the vacancy defects exert a significant deterioration of the average nanotube natural frequency to 79.5% and 81.5% of a perfect structure for armchair and zigzag configuration, respectively. The results demonstrate that defect recovery can restore the nanotube natural frequency to 93.8% and 94.6% of a perfect structure for armchair and zigzag configuration, respectively. These findings can pave the way to design ultra-high resolution CNT-based nano-sensors using defective and recovered/reconstructed CNTs.